"It Is Not Something You Can Easily Forget": Ghanaian Parents' Experiences of Child Loss. (December 2022) - Asare, Grace Owusu; Annor, Francis; Yendork, Joana Salifu
The loss of a child comes with trauma, which affects parents and the entire family. Yet, there is limited support for parents who lose their child and little empirical research has been devoted to the experiences of parents who lose a child in the Ghanaian context. Based on interviews with 20 participants purposively sampled from the Accra Metropolis, this study explored parents' psychosocial experiences of child loss using a qualitative approach. The study's findings indicated that bereaved parents showed signs of complicated grief and experienced spousal neglect, self-blame, and emotional pain. Bereaved parents may become sensitive to child comments years after child loss. The quality of interaction after child loss influences how parents experience the loss. Findings underscore the need for a joint effort by government and other stakeholders in the health sector to address issues related to child loss and provide improved services to those who suffer child loss.